2007
DOI: 10.1007/s00114-007-0310-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and faunal implications of Early Cretaceous deinonychosaur trackways from China

Abstract: Deinonychosaurian theropods, the dinosaurian sister group of birds, are characterized by a large raptorial claw borne on a highly modified second digit that was thought to be held in a retracted position during locomotion. In this study, we present new trackway evidence for two coeval deinonychosaurian taxa from the Early Cretaceous of Shandong, China that indicate a hitherto unrecognized body size diversity for this period and continent. These fossil tracks confirm diversity and locomotory patterns implied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 25 publications
3
59
0
2
Order By: Relevance
“…All in all this demonstrates that morphotypes very similar to the Jurassic ichnotaxa Eubrontes, Megalosauripus, Anchisauripus, and Grallator (Olsen et al, 1998) are widely distributed in Lower Cretaceous deposits of China Xing, Lockley, Marty et al, 2015). However, Early Cretaceous Eubrontes tracks generally have larger digit divarication angles than Early Jurassic representatives ; but see Ahlberg, 1994 andLucas et al, 2006 (Kim, Kim, & Lockley, 2008), Dromaeosauripus yongjingensis , and Dromaeopodus shandongensis (Li et al, 2007) Lockley, Gierlinski et al, 2014). Deinonychosaurian tracks are also recorded from Xiaoba Formation of the Panxi region and belong to the Velociraptorichnus morphotype (Xing et al, in press).…”
Section: Comparison and Discussionmentioning
confidence: 89%
“…All in all this demonstrates that morphotypes very similar to the Jurassic ichnotaxa Eubrontes, Megalosauripus, Anchisauripus, and Grallator (Olsen et al, 1998) are widely distributed in Lower Cretaceous deposits of China Xing, Lockley, Marty et al, 2015). However, Early Cretaceous Eubrontes tracks generally have larger digit divarication angles than Early Jurassic representatives ; but see Ahlberg, 1994 andLucas et al, 2006 (Kim, Kim, & Lockley, 2008), Dromaeosauripus yongjingensis , and Dromaeopodus shandongensis (Li et al, 2007) Lockley, Gierlinski et al, 2014). Deinonychosaurian tracks are also recorded from Xiaoba Formation of the Panxi region and belong to the Velociraptorichnus morphotype (Xing et al, in press).…”
Section: Comparison and Discussionmentioning
confidence: 89%
“…However, the fossil evidence clearly shows trackways spread across several orientations and it is not known why the authors decided to interpret this as evidence of gregariousness when the tracks are so highly random. Matsukawa et al (1997) described a detailed trackway left by 33 members of the inchnogenera Toyamasauripus masuiae from the early Cretaceous beds of Toyama prefecture in central Japan and from Shandong, China, Li et al (2007) reported both closely spaced and multiple parallel trackways considered as evidence for group travel in deinonychosaurs, though no inference to pack hunting was made. The Winton Formation in Queensland, Australia, is famed for the Lark Quarry site which boasts trackways preserved in an ancient mudflat of over 130 small theropod and ornithopod dinosaurs, which apparently went into a stampede triggered by the approach of an individual large theropod Wade 1979, 1984).…”
Section: Te Isles 156mentioning
confidence: 99%
“…This is faster than that of Dromaeosauripus yongjingensis (0.75 m/s, Xing et al, 2012), slower than that of Dromaeopodus shandongensis (1.63 m/s; Li et al, 2007;Kim et al, 2008), and much slower than Dromaeosauripus hamanensis (4.86 m/s, Kim et al, 2008).…”
Section: Ichnotaxonomy and Trackmaker Identificationmentioning
confidence: 84%